2009
DOI: 10.1093/toxsci/kfp216
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics Applied to Cultures of Human Hepatocytes Enabled an Identification of Novel Petasites hybridus Extracts for the Treatment of Migraine with Improved Hepatobiliary Safety

Abstract: Butterbur extracts (Petasites hybridus) are recommended for the prevention of migraine, but pharmacovigilance reports may be suggestive of rare hepatobiliary toxicity. To evaluate its hepatotoxic potential, a series of in vivo and in vitro studies were carried out. Essentially, there were no signs of hepatocellular toxicity at estimated therapeutic C(max) levels of 60 ng/ml. Nonetheless, in a 28-day toxicity study at approximately 200-fold of therapeutic doses, induced liver transaminases and bilirubin elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…However, recent studies indicated that there were no signs of hepatocellular toxicity at estimated therapeutic C max levels of 60 ng/mL. Nonetheless, when investigating liver function in vitro at >170-fold of therapeutic C max levels, including cytotoxicity (measured by conversion of tetrazolium bromide (MTT) to MTT formazan, intracellular ATP using ATP bioluminescence and lactate dehydrogenase (LDH) activity), transaminase activities (alanine aminotransferase and aspartate aminotransferase), albumin synthesis, urea and testosterone metabolism to assay for cytochrome P450 monooxygenase activity, only rhizome extracts rich in petasin (37% petasin) evoked liver toxicity (Anderson et al, 2009). Lipophilic extracts of Petasites hybridus rhizomes with different content of petasin and isopetasin were investigated for an inhibition of COX-1 and -2 isoenzymes, whereas inhibition of the expression of COX-2 and p42/44 MAP kinase was tested in rat primary microglial cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies indicated that there were no signs of hepatocellular toxicity at estimated therapeutic C max levels of 60 ng/mL. Nonetheless, when investigating liver function in vitro at >170-fold of therapeutic C max levels, including cytotoxicity (measured by conversion of tetrazolium bromide (MTT) to MTT formazan, intracellular ATP using ATP bioluminescence and lactate dehydrogenase (LDH) activity), transaminase activities (alanine aminotransferase and aspartate aminotransferase), albumin synthesis, urea and testosterone metabolism to assay for cytochrome P450 monooxygenase activity, only rhizome extracts rich in petasin (37% petasin) evoked liver toxicity (Anderson et al, 2009). Lipophilic extracts of Petasites hybridus rhizomes with different content of petasin and isopetasin were investigated for an inhibition of COX-1 and -2 isoenzymes, whereas inhibition of the expression of COX-2 and p42/44 MAP kinase was tested in rat primary microglial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Written approval for the use of human liver specimens was obtained from patients undergoing hepatic resections with approval of the ethics committee of the Medical School of Hannover. Details regarding the isolation and culture of human hepatocytes in the collagen sandwich were previously described [41].…”
Section: Methodsmentioning
confidence: 99%
“…An illustrative example how TGx facilitates the detection of hepatotoxicity not visible in animal experiments was given by Anderson et al (2009). An illustrative example how TGx facilitates the detection of hepatotoxicity not visible in animal experiments was given by Anderson et al (2009).…”
Section: Herbal Hepatotoxicity and Toxicogenomicsmentioning
confidence: 99%